Serum phosphate levels and the development of sepsis associated acute kidney injury: evidence from two independent databases - Fang, Yipeng; Zhang, Yuan; Zhang, Xin (Frontiers in Medicine, 2024)
We aimed to investigate the association between serum phosphate levels and the risk for developing sepsis associated acute kidney injury (SAKI).Methods: Septic patients from the Medical Information Mart for Intensive Care IV (MIMIC IV) and the eICU Collaborative Research Database (eICU-CRD) were enrolled. Restricted cubic spline (RCS) was used to visualize the relationship between phosphate levels and the risk of SAKI. Patients were divided into four categories based on their serum phosphate levels. Logistic regression analysis, receiver operating characteristic (ROC) curve and subgroup analysis were performed to evaluate the predictive value of serum phosphate for SAKI.Results: A total of 9244 and 2124 patients from the MIMIC IV and eICU-CRD database were included in the final analysis. RCS curve revealed a non-linear correlation between phosphate levels and the risk of SAKI (p for non-linearity < 0.05). Each 1mg/dL increase in phosphate levels was associated with a 1.51 to 1.64-fold increased risk of SAKI (OR 2.51-2.64, p< 0.001) in the MIMIC IV cohort and a 0.29 to 0.38-fold increased risk (OR 1.29-1.38, p< 0.001) in the eICU-CRD cohort. Compared to the normal-low category, hyperphosphatemia and normal-high category were independently associated with an increased risk of SAKI, while hypophosphatemia was independently associated with a decreased risk in the MIMIC IV cohort. A similar trend was observed in the eICU-CRD cohort, but statistical significance disappeared in the hypophosphatemia category and the adjusted model of normal high category. These finding was consistent in subgroup analysis. Conclusions: Elevated serum phosphate, even within the normal range, is an independent risk factor for developing SAKI in septic patients. Abnormal change in serum phosphate levels may be a novel biomarker for early prediction of SAKI occurrence.